Regional variation and social context in Limola society - Budiono, Satwiko; Sukesti, Restu; Yanita, Selly Rizki; Jaya, Taufan; Khairiah, Dewi (Research Journal in Advanced Humanities, 2025)
Limola language in Sassa Village, Baebunta District, North Luwu Regency, South Sulawesi Province, Indonesia, is included in the minority language with a critical language status. The dominance of other languages makes this language have an alternative name, namely Lemolang language. This name was given by Tae language speakers who are more dominant in North Luwu Regency. This dominance makes the name Lemolang better known than Limola. This is because the people in Sassa Village prefer to use Tae language in everyday communication. In connection with this, this study examines language variations in Sassa Village. This aims to correct the name of the Lemolang language to Limola empirically. In addition, this study also aims to identify the language situation in Sassa Village. The research method uses a mixed method, both quantitative and qualitative. Data collection techniques include interviews and direct observation. Data analysis of this study was carried out using a dialectological and sociolinguistic approach. The results of the study show that Sassa Village has five languages, namely Limola, Tae, Rampi, Javanese, and Sasak. The many language variations in Sassa Village are due to the presence of immigrants through the transmigration program in the past.